2000
DOI: 10.1023/a:1007259810190
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Toxigenic saprophytic fungi were isolated from samples of shellfish, sediment and seawater obtained from marine shellfish farming areas. The 456 strains identified included 12 different genera, with a clear predominance (68%) of Penicillium, Aspergillus, Trichoderma and Cladosporium. To assess the risk of poisoning due to the presence of these fungi in shellfish farming areas, the strains were cultured in liquid medium, filtered, and tested on larvae of Artemia salina, a small crustacean highly sensitive to my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 6 publications
3
33
0
Order By: Relevance
“…Next-generation sequencing-based studies are rare, except Arfi et al (2012) who investigated the anoxic mangrove sediments of Saint Vincent Bay, and revealed that Agaricomycetes was the dominant fungal class. As a result, insufficient information on the fungal community in the sediment of intertidal ecosystems is hindering our understanding of their ecological functions (González et al, 1998; Sallenave-Namont et al, 2000; Rämä et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Next-generation sequencing-based studies are rare, except Arfi et al (2012) who investigated the anoxic mangrove sediments of Saint Vincent Bay, and revealed that Agaricomycetes was the dominant fungal class. As a result, insufficient information on the fungal community in the sediment of intertidal ecosystems is hindering our understanding of their ecological functions (González et al, 1998; Sallenave-Namont et al, 2000; Rämä et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Aspergillus, Penicillium, Trichoderma and Cladosporium ). Therefore, the study conducted by Sallenave-Namont et al (2000) confirmed the existence of fungi producing mycotoxins in shellfish farming areas in France.…”
Section: Aetiology and Effects Of Shell Disease In Molluscsmentioning
confidence: 83%
“…Sallenave-Namont et al (2000) isolated possible toxigenic saprotrophic fungi from samples of shellfish ( Cerastoderma edule, Mytilus edulis ), sediments and seawater from shellfish farming areas and from natural shellfish beds along the coast of France. Filtrates from the media used to grow the fungi were tested for their effects on larvae of the small crustacean Artemia salinus , which is highly sensitive to mycotoxins.…”
Section: Aetiology and Effects Of Shell Disease In Molluscsmentioning
confidence: 99%
“…-Trichoderma species have been isolated before from marine sediments in Japan and South China [24], and in France [7]. Their ability to grow in hypersaline environment has been demonstrated under laboratory marine-like culture conditions [8], but they have never been directly observed in the natural marine environment.…”
Section: Mass-spectrometric Elucidation Of Peptaibol Structures and Smentioning
confidence: 99%
“…The hypothesis of a fungal contamination with a production of toxic metabolites has been proposed. Isolation of fungi from shellfish and sediments collected in farming areas showed that numerous saprophytic strains -mainly belonging to the genera Aspergillus, Penicillium, or Trichoderma -were present in these zones [7]. Toxicities of these strains were studied using different biological tests on laboratory cultures realized in marine-like conditions.…”
mentioning
confidence: 99%